PENERAPAN METODE PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION (TAI) UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN SIMULASI DIGITAL KELAS X RPL DI SMK NEGERI 4 PAYAKUMBUH - Nova Perdana Roza Putri; Efrizon Efrizon; Titi Sriwahyuni (Universitas Negeri Padang, 2018)
The purpose of this research is to reveal the magnitude of the percentage of the influence of the application of Team Assisted Individualization (TAI) learning method with direct learning model on the subjects of Digital Simulation class X Software Engineering semester odd SMK Negeri 4 Payakumbuh Year Teaching 2017/2018. This type of research is quantitative using experimental type quasi experimental design research method. This research was conducted at SMK Negeri 4 Payakumbuh on 15 October until 15 November 2017. Population in this research that is student of class X, XI, XII RPL SMK Negeri 4 Payakumbuh. Sampling technique used is probability sampling with simple random sampling technique. The selected to be samples in this study are students of class X RPL2 experimental class and X1 RPL1 as control class. Based on the result of the research, the average of learning result of the experimental class is 82,71, while the control class get the average value 79,34. The result of hypothesis calculation at significant level α = 0,05 got tcount>ttable that is (3,64> 1, 6668), because big tcount of ttable, null hypothesis (H0) rejected and alternative hypothesis (Ha) accepted. This means that Team Assisted Individualization (TAI) learning method has a positive effect on the learning outcomes Digital Simulation students of class X SMK Negeri 4 Payakumbuh.Keywords: Learning outcomes, Team Assisted Individualization (TAI) learning methods, direct learning models